Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/172560
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Modeling of Residual Stress Development in Continuous Fiber-Reinforced Unidirectional Thick Thermoset Composites

Abstract: The primary objective of this research is to develop a multiscale simulation framework to arrive at more realistic estimates of cureinduced residual stresses in the vicinity of the fiber-matrix interface in thick thermoset composites. The methodology involves simulations at the part level-employing homogenized rendering of the composite using micromechanics approach-within a finite element framework to obtain part-level temperature and degree-of-cure gradients and strains, and imposition of this information as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The kinetics model for curing process has been taken for a polyester resin from Patham et. al 7 . Although, the mechanical properties of these cured resins differ significantly, both the resin systems exhibit similar fashion kinetics and follow Arrhenius equation during curing process.…”
Section: Formulation and Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…The kinetics model for curing process has been taken for a polyester resin from Patham et. al 7 . Although, the mechanical properties of these cured resins differ significantly, both the resin systems exhibit similar fashion kinetics and follow Arrhenius equation during curing process.…”
Section: Formulation and Proceduresmentioning
confidence: 98%
“…There have been many studies to understand the volumetric change and development of residual stress during the curing process. 1,7,8 However, many of these studies assume an oversimplified constitutive behavior of the resin, 7,9,10 thus leading to unrealistic (over-predicted) residual stresses in the composites. Raheem et al 11 studied the effect of different curing conditions on properties like hardness, thickness, and residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of thermal expansion (CTE) is different in different directions for composite materials. Previous experimental studies have shown that the CTE of resin-dominated directions is much higher than that of fiber-dominated directions [20,21]. The stresses get built up on the fiber-matrix, lamina-laminate, and structural levels.…”
Section: Introductionmentioning
confidence: 95%